FORMATION OF STUDENTS 'READINESS FOR CREATIVE ACTIVITY BY EDUCATIONAL MEANS WORKS (Pedagogy of Higher and Secondary Education, 2001)
This article deals with various problems of forming readiness for creative pedagogical activities and making optimum conditions of pedagogical process. The author considers several practical methods of developing teachers-to-be creative qualities in the school of higher learning.